Trends in head injury mortality among 0–14 year olds in Scotland (1986–95). Issue 4 (1st April 2002) - Williamson, L M; Morrison, A; Stone, D H
Abstract : Study objective: To examine the trends in childhood head injury mortality in Scotland between 1986 and 1995. Design: Analysis of routine mortality data from the registrar general for Scotland. Setting: Scotland, UK. Subjects: Children aged 0–14 years. Main results: A total of 290 children in Scotland died as a result of a head injury between 1986 and 1995. While there was a significant decline in the head injury mortality rate, head injury as a proportion of all injury fatalities remained relatively stable. Boys, and children residing in relatively less affluent areas had the highest head injury mortality rates. Although both these groups experienced a significant decline over the study period, the mortality differences between children in deprivation categories 1–2 and 6–7 persisted among 0–9 year olds, and increased in the 10–14 years age group. Pedestrian accidents were the leading cause of mortality. Conclusions: Children residing in less affluent areas seem to be at relatively greater risk of sustaining a fatal head injury than their more affluent counterparts. While the differences between the most and least affluent have decreased overall, they have widened among 10–14 year olds. The decline in head injury mortality as a result of pedestrian accidents may be partly attributable to injury prevention measures.